MANAJEMEN LABA - Lilis Setiawati; Ainun Na'im (Faculty of Economics and Business, Universitas Gadjah Mada, 2000)
This paper is intended to explain manager responsibility in managing opportunities to choose accounting methods for external reporting, so that the reported earnings information will not mislead investors. Earnings management is a purposeful intervention in the external financial reporting process, with the intent to obtain some private gains (Schipper, 1989, 92). Opportunity to manage earnings as a consequence of our current accounting system can not be eliminated. The problem is earning management can influence investor decisions.